Measurement and Modelling of The Force Required to Move Coalesced Oil Droplets along Oleophillic and Oleophobic Fibres. - Mullins, Benjamin; Mead-Hunter, Ryan; Kasper, G.; King, Andrew (Curran Associates, 2011)
This paper presents the results of an extensive series of measurements of droplet-fibre forces in mist (coalescing) filters. A method was developed which allowed droplet-fibre forces to be measured using an Atomic Force Microscope (AFM). The AFM was also be utilised to measure the surface roughness of filter fibres, which was found to significantly affect the results. A theoretical model was also developed to predict the droplet fibre forces, based on wetting theory. Measurements of forces on polymer fibres are presented here, along with the same fibres after coating with a fluorinated copolymer coating to render them oleophobic. The oloephillic results show good agreement with the theoretical model. The phobic results differ significantly from the phillic, and a model is currently being developed for this case. Such measurements are vital for validating CFD models such as the one being developed by the authors.